Low-Frequency Fatigue as an Indicator of Eccentric Exercise-Induced Muscle Injury: The Role of Vitamin E. (10th July 2012) - Kyparos, Antonios; Nikolaidis, Michalis G.; Dipla, Konstantina; Zafeiridis, Andreas; Paschalis, Vassilis; Grivas, Gerasimos V.; Theodorou, Anastasios A.; Albani, Maria; Matziari, Chrysoula; Vrabas, Ioannis S.
Abstract : This study investigates whether vitamin E can attenuate eccentric exercise-induced soleus muscle injury as indicated by the amelioration of in situ isometric force decline following a low-frequency fatigue protocol (stimulation at 4 Hz for 5 min) and the ability of the muscle to recover 3 min after the termination of the fatigue protocol. Adult male Wistar rats were divided into vitamin E-supplemented or placebo-supplemented groups studied at rest, immediately post-exercise or 48 h post-exercise. Daily d l - α -tocopheryl acetate intraperitoneal injections of 100 mg/kg body mass for 5 consecutive days prior to exercise doubled its plasma levels. Fatigue index and recovery index expressed as a percentage of the initial tension. FI at 0 h post- and 48 h post-exercise respectively was 88% ± 4.2% and 89% ± 6.8% in the vitamin E groups versus 76% ± 3% and 80% ± 11% in the placebo groups. RI was 99% ± 3.4% and 100% ± 6% in the vitamin E groups versus 82% ± 3.1% and 84% ± 5.9% in the placebo groups. Complementally to the traditionally recorded maximal force, low-frequency fatigue measures may be beneficial for assessing injury-induced decrease in muscle functionality.